Van Wyk- Grumbach Syndrome An Unusual Presentation of Severe Hypothyroidism (Journal of Armed Forces Medical College, Bangladesh, 2016)
Van Wyk- Grumbach syndrome (VWGS) is characterized by juvenile hypothyroidism, delayed bone age, and precocious puberty with a complete reversal to the pre-pubertal state following thyroid hormone replacement therapy. In this study, a 7 years and 1 month old girl presented with precocity having premature menarche, short stature, constipation, delayed bone age and enlarged bilateral multicystic ovaries. She presented with acute abdomen due to torsion of left ovary and had to undergo left sided oophorectomy and right ovarian cystectomy. High serum TSH, low FT4 with high FSH but low LH within pre-pubertal range suggestive of severe hypothyroidism with FSH dominant precocious pseudopuberty confirmed the diagnosis of VWGS.Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 85-88